CRNDE enhances the expression of MCM5 and proliferation in acute myeloid leukemia KG-1a cells by sponging miR-136-5p - Chen Liu (Nature Portfolio, 2021)
Abstract The long-noncoding RNA colorectal neoplasia differentially expressed (CRNDE) gene has been considered to be crucial in tumor malignancy. Although CRNDE is highly expressed in acute myeloid leukemia (AML), its mechanism of action remains unknown. In this study, GEPIA and qRT-PCR were performed to confirm the expression of CRNDE in AML samples and cell lines, respectively. CRNDE shRNA vectors were transfected to explore the biological functions of CRNDE. The cell proliferation was assessed by the CCK8 assay, while apoptosis and cell cycle distribution were measured by flow cytometry and Western blotting. The results showed that CRNDE was overexpressed in both AML samples and cell lines. CRNDE silencing inhibited proliferation and increased apoptotic rate and cell cycle arrest of KG-1a cells. The luciferase reporter assay coupled with RIP assay revealed that CRNDE act as a ceRNA. Rescue assays demonstrated that the effects of CRNDE silencing could be reversed by miR-136-5p inhibitors. In conclusion, our results expound that the CRNDE/miR-136-5p/MCM5 axis modulates cell progression and provide a new regulatory network of CRNDE in KG-1a cells.